Factors Predicting Sexual Behaviors in Colorectal Cancer Survivors - Srifah, Kanyapat; Saneha, Chongjit; Sriprasong, Sarinrut; Soparattanapaisarn, Nopadol (Nursing Science Journal of Thailand, 2022)
Purpose: To study the sexual behaviors of colorectal cancer survivors and the predictive power of perceived sexual barriers, perceived sexual self-efficacy, sexual anxiety, and sexual depression on the sexual behaviors of colorectal cancer survivors. Design: Predictive correlational study. Methods: The study was conducted in 85 colorectal cancer survivors aged 18 years and over who had completed cancer treatment for at least three months. Data were collected by using 6 questionnaires: a demographic, perceived sexual barriers, perceived sexual self-efficacy, sexual anxiety, sexual depression, and sexual behaviors. The data were analyzed by using descriptive and multiple regression statistics. Main findings: The results showed that the average age of the participants was 64.6 years (SD = 7.01). The average score of participants’ sexual behaviors was medium level which was the same level as before. The results of multiple regression analysis showed that perceived sexual barriers, perceived sexual self-efficacy, sexual anxiety, and sexual depression were able to jointly explain 33% of the variance of sexual behaviors in colorectal cancer survivors. Perceived sexual self-efficacy ( = .26, p < .05), perceived sexual barriers ( = - .28, p < .01) and sexual depression ( = - .27, p < .05) were statistically significant predictors of sexual behaviors. Conclusion and recommendations: According to the study findings, perceived sexual barriers, perceived sexual efficacy, and sexual depression were able to predict the sexual behaviors with statistical significance. Nurses and healthcare providers should assess sexual behaviors, perceived sexual barriers, perceived sexual self-efficacy, and sexual depression of the colorectal cancer survivors in order to manage these factors resulting in improvement in survivors’ sexual behaviors.